hich equations are equivalent to y = two-thirds x minus 4 when written in slope-intercept form? Check all that apply. 3 x minus 2 y = 4 2 x minus 3 y = 12 Negative 4 (2 x minus 3 y) = negative 4 (12) 2 (x + 6) = 3 y 2 x minus 3 y = 4

Answer :

MrRoyal

Answer:

[tex]2x - 3y = 12[/tex]

[tex]-4(2x - 3y) = -4(12)[/tex]

Step-by-step explanation:

Given

[tex]y = \frac{2}{3}x - 4[/tex]

Required

Equivalents of the given equation;

We start by multiply both sides of the equation by 3

[tex]3* y = 3(\frac{2}{3}x - 4)[/tex]

[tex]3y = 3 * \frac{2}{3}x - 3 * 4[/tex]

[tex]3y = 2x - 12[/tex] ---- Equation 1

Subtract 3y from both sides

[tex]-3y + 3y = 2x - 12 - 3y[/tex]

[tex]0 = 2x - 12 - 3y[/tex]

Add 12 to both sides

[tex]12 + 0 = 2x - 12 - 3y + 12[/tex]

[tex]12 = 2x - 3y[/tex]

Rearrange:

[tex]2x - 3y = 12[/tex] ---- This is equivalent to the given equation;

Multiply both sides of the above equation by -4

[tex]2x - 3y = 12[/tex]

[tex]-4(2x - 3y) = -4(12)[/tex]  ---- This is also equivalent to the given equation;

From the list of given options, only these two are equivalent to [tex]y = \frac{2}{3}x - 4[/tex]

Toxictaco1

Answer:

Answer:

Step-by-step explanation:

Given

Required

Equivalents of the given equation;

We start by multiply both sides of the equation by 3

---- Equation 1

Subtract 3y from both sides

Add 12 to both sides

Rearrange:

---- This is equivalent to the given equation;

Multiply both sides of the above equation by -4

 ---- This is also equivalent to the given equation;

From the list of given options, only these two are equivalent to

Step-by-step explanation:

Other Questions